Mechanical and thermal properties of fumed silica-incorporated silane-terminated urethane/epoxy-interpenetrating polymer network nanocomposites - AKIN, EMRE; ÇAKIR, MUSTAFA; KARTAL, İLYAS (My University, 2024)
In this study, it was aimed to improve the mechanical and thermal properties of epoxy materials based on diglycidyl ether of bisphenol-A-based. For this purpose, three different nanocomposite materials were prepared at various ratios including a fumed silica nanoparticle-reinforced epoxy nanocomposite (FSN), an epoxy/silane-terminated urethane (STU) hybrid interpenetrating polymer network (IPN) nanocomposite (SHIN), and a fumed silica-reinforced epoxy/STU hybrid IPN nanocomposite (FSHIN). While synthesizing SHIN, 3-isocyanato propyl trimethoxy silane (ICPTMS) and poly (hexamethylene carbonate) diol were used. The synthesized STU polymer chains were crosslinked by reacting them with TEOS via the sol–gel process. Therefore, hybrid networks were obtained. Moreover, fumed silica nanoparticles were incorporated into the hybrid networks via the sol–gel process for FSHINs. The three different nanocomposite materials exhibited much more improved properties than the neat epoxy. The most prominent nanocomposite was FSHIN. In comparison with the neat epoxy, Young\"s modulus, ultimate tensile strength, and Izod impact resistance values increased at ratios of 53%, 50%, and 223%, respectively. Glass transition temperature values and char yield values increased substantially in all nanocomposites. However, thermal decomposition temperatures increased only for FSNs. Moreover, these values for FSHINs that were very close to those of the neat epoxy were considerably higher than those of SHINs. Highlights: Fumed silica-incorporated silane-terminated urethane/epoxy IPN nanocomposites. Substantially improved mechanical properties and impact resistance. Improved thermal stability.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya; Fizik Bilimleri; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Polymers and Plastics; Materials Chemistry; hybrid networks; interpenetrating polymer networks; nanocomposite; silane-terminated urethanes